2019
DOI: 10.3389/fneur.2019.00247
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Reductions of Subcortical Structures and Their Localizations in Alcohol-Dependent Patients

Abstract: Changes in brain morphometry have been extensively reported in various studies examining the effects of chronic alcohol use in alcohol-dependent patients. Such studies were able to confirm the association between chronic alcohol use and volumetric reductions in subcortical structures using FSL (FMRIB software library). However, each study that utilized FSL had different sets of subcortical structures that showed significant volumetric reduction. First, we aimed to investigate the reproducibility of using FSL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…A comprehensive neurobiological understanding of alcohol reactivity is critical for identifying the neuropathology of AUD and developing appropriate treatments to reduce relapse (36). AUD is marked by widespread gray and white matter damage in selected neural circuits (38). Morphometric magnetic resonance imaging (MRI) studies have reported reduced volume in cortical and subcortical cerebral structures in patients with AUD.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive neurobiological understanding of alcohol reactivity is critical for identifying the neuropathology of AUD and developing appropriate treatments to reduce relapse (36). AUD is marked by widespread gray and white matter damage in selected neural circuits (38). Morphometric magnetic resonance imaging (MRI) studies have reported reduced volume in cortical and subcortical cerebral structures in patients with AUD.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking has been associated with smaller nucleus accumbens 6,7 , amygdala 79 , hippocampus 10 , pallidum 9 and thalamus 7,9,11 volumes, to smaller 8 and larger 12 caudate volume, and to larger putamen volume 6 . Alcohol (ab)use has been associated with smaller nucleus accumbens 13,14 , amygdala 15 , hippocampus 13,14,16 , pallidum 14,17 and with smaller 18 and larger 19 caudate, smaller 13,14,16 and larger 20 thalamus and smaller 14 and larger 20 putamen volumes. Recently, the ENIGMA addiction working group attempted to resolve these inconsistent findings with a mega-analysis of subcortical thickness and surface area (volume being its product), among 1,628 controls and 2,277 individuals with dependence on alcohol, nicotine, cocaine, methamphetamine, and/or cannabis 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The adult high-risk drinking rate is 14.2% in South Korea, and the onset of alcohol drinking is 13.3 years. 1 In addition, 16.9% of adolescents drink alcohol more than once within 30 days and half of them are high-risk alcohol drinkers. 1 Early onset of drinking in adolescents is relevant to alcohol-related problems in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Previous studies have reported that chronic alcohol consumption causes negative changes in CA3 synapses in the hippocampus and a decrease in hippocampal volume in both human beings and animal models. [13][14][15][16] Binge alcohol use in adolescence also causes mitochondrial impairment in the hippocampus, and its damage continues into adulthood. 17 Recently, the effects of alcohol on the hippocampus at the cellular and molecular levels have been studied through large-scale transcriptome profiling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation